Peer-mediated instruction improves acquisition of complex wrestling techniques in school physical education - Salih Gürsoy; Aylin Zekioglu (PLoS ONE, 2026)
This study investigated the effectiveness of peer-mediated instruction as a student-centered teaching method in physical education by assessing its impact on middle school students’ ability to learn complex wrestling techniques. A total of 36 students took part in an eight-week program comparing peer-mediated instruction with traditional direct instruction. Performance on four wrestling techniques—arm drag, underarm pass, single-leg takedown, and double-leg takedown—was evaluated using standardized observation criteria and independent raters. Results from independent-samples t-tests indicated that students in the peer-teaching group performed significantly better on the underarm pass, t(34) = 3.976, p = .001, d = 1.33, and the double-leg takedown, t(34) = 2.31, p = .027, d = 0.78. No significant differences between groups were found for the arm drag, t(34) = 1.685, p = .101, d = 0.55, or the single-leg takedown, t(34) = 0.52, p = .606, d = 0.18. These results suggest that peer-mediated instruction may be more effective than direct instruction for techniques that demand higher perceptual-motor coordination and involve greater task complexity. The study adds to the sport pedagogy literature by demonstrating that peer-assisted learning can support skill development and collaborative participation in school-based physical education.